1981
DOI: 10.1029/jb086ib10p09411
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐flow determination in three DSDP boreholes near the Japan Trench

Abstract: The first deep borehole determinations of temperature gradients and heat flow on the landward wall of the Japan Trench and forearc were made on IPOD DSDP leg 57. These heat flow values are based on temperature logs corrected to equilibrium, using a detailed model of the drilling disturbance. Heat flow values on a deeply submerged marine terrace, landward of the trench slope break are 28 and 32 mW m−2. A measurement in the midslope terrace basin on the landward wall of the trench yielded a value of 22 mW m−2. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Estimated heat fluxes in the area are 0.6-2.5 mW m À 2 , which is markedly less than the terrestrial heat flow values of 22-32 mW m À 2 observed in the Japan Trench 33 . Helium may diffuse faster and farther than heat, which is well documented around the Ontake Volcano, Japan 34 .…”
Section: Discussionmentioning
confidence: 89%
“…Estimated heat fluxes in the area are 0.6-2.5 mW m À 2 , which is markedly less than the terrestrial heat flow values of 22-32 mW m À 2 observed in the Japan Trench 33 . Helium may diffuse faster and farther than heat, which is well documented around the Ontake Volcano, Japan 34 .…”
Section: Discussionmentioning
confidence: 89%
“…This similarity lends great credence to the technique of determining conductivity indirectly from porosity and mineralogy data, although the accuracy of the technique could have been better assessed if the temperature log had been made more carefully (cf., Burch and Langseth, 1981). Nevertheless, this method appears to provide a good estimate of the average conductivity, and it should be useful in obtaining heat-flow estimates at sites where no direct conductivity measurements are made, oil wells, for example.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the excess temperature measured near seafloor is that the upper part of the hole was warmed by the drilling fluid returning to seafloor from the hole bottom at a temperature significantly higher than the bottomwater temperature. Circulation rates lower than 25 L/s could produce this situation (Burch and Langseth, 1981). Circulation rates in holes of Site 808 were between 15 and 45 L/s.…”
Section: Hole 808ementioning
confidence: 99%